REPRESENTASI EKOFEMINISME DALAM NOVEL BILANGAN FU (Universitas Negeri Surabaya, 2023)
This research was aimed to determined of ecofeminism discourse which was formed through a novel entitled Bilangan Fu by Ayu Utami published in 2008. This research is a descriptive qualitative research with Teun A. Van Djik’s discourse analysis method. Data collection was obtained from novel texts, reader interviews, and literature study. Data analysis techniques was performed with conclude and verify from observation obtained from text analysis, interviews, and documentation. The result of this research indicate that the representation of ecofeminism discourse raised by the author through the character, narrative, and story telling in the novel shows about the relations between women and nature. It was supported by the situation and socio culture context that was relevant to the description in the story setting.